Financing governance institutions in Ghana: The case of the National Commission on Civic Education (Journal of Governance and Development (JGD), 2014)
This paper examines how the NCCE has been affected in the performance of its constitutional functions by inadequate funding. Created in 1993 by Ghana’s Constitution to serve as one of the anchors of democracy, the NCCE has suffered a perennial lack of funds. Analyzing primary data from survey carried on officials of the NCCE and policy makers, the article discovered abysmal performance of the NCCE largely due to its inability to receive adequate funding. Respondents attributed NCCE’s financial paucity partly to its partisan complexion, which has also made it less attractive to donor funding. Despite the financial difficulties, the NCCE has managed to pursue public education on Ghana’s constitution, campaigned against election and ethnic violence through the parsimonious use of its meager resources. The NCCE can overcome its financial challenges if government can set up a Civic Fund where a fixed percentage of gross national product would be allocated to the NCCE to run its planned programs.